Evaluation of Cultural Impact on Regional Economic Development in Russia - Lukashenko, Inna V.; Fedorova, Elena A. (Journal of Reviews on Global Economics, 2018)
Paper is devoted to Dependence of economic development of the Russian regions on their cultural level indicators. It determines and analyzes the influence degree of cultural components of the region development on its economic factors. The investigated statistical base consists of selected cultural and economic indices taken in the period of 2000-2015 years. The hypothesis of significant influence degree of the visits to museums and in particular, theatres number, on the amount of implemented innovational technologies was confirmed. A hypothesis about the close relationship between the volumes of expenditures of the Russian budget for culture and the level of research and development work, as well as directly the number of innovative industrial technologies introduced was confirmed. Hypotheses about the close interaction of cultural indices and such macroeconomic parameters as GDP growth, the volume of the capital investments have not been confirmed. A weak correlation between library holdings volume and the studied economic indicators was noted. The research can be used in design of the regional development programs, in forming budget priorities of budgets projects, or in taking other management decisions programming the basis for effective social and economic policy of the regions.